Non-steroidal anti-inflammatory drugs induce immunogenic cell death in suppressing colorectal tumorigenesis - Fletcher, Rochelle (Oncogene, 2021)
Use of non-steroidal anti-inflammatory drugs (NSAIDs) is associated with reduced risk of colorectal cancer (CRC). However, the mechanism by which NSAIDs suppress colorectal tumorigenesis remains unclear. We previously showed that NSAIDs selectively kill emerging tumor cells via death receptor (DR) signaling and a synthetic lethal interaction mediated by the proapoptotic Bcl-2 family protein BID. In this study, we found NSAIDs induce endoplasmic reticulum (ER) stress to activate DR signaling and BID in tumor suppression. Importantly, our results unveiled an ER stress- and BID-dependent immunogenic effect of NSAIDs, which may be critical for tumor suppression. NSAID treatment induced hallmarks of immunogenic cell death (ICD) in CRC cells and colonic epithelial cells upon loss of APC tumor suppressor, and elevated tumor-infiltrating lymphocytes (TILs) in the polyps of APC(Min/+) mice. ER stress inhibition or BID deletion abrogated the antitumor and immunogenic effects of NSAIDs. Furthermore, increased ER stress and TILs were detected in human advanced adenomas from NSAID-treated patients. Together, our results suggest that NSAIDs induce ER stress- and BID-mediated ICD to restore immunosurveillance and suppress colorectal tumor formation.